Ganetespib with Methotrexate Acts Synergistically to Impede NF-κB/p65 Signaling in Human Lung Cancer A549 Cells - Gehad Subaiea; Syed Mohd Danish Rizvi; Hemant Kumar Singh Yadav; Turki Al Hagbani; Marwa Helmy Abdallah; El-Sayed Khafagy; Hosahalli Veerabhadrappa Gangadharappa; Talib Hussain; Amr Selim Abu Lila (MDPI AG, 2023)
Among the various types of cancer, lung cancer accounts for the highest number of fatalities across the globe. A combination of different cancer chemotherapeutics is regarded as an effective strategy for clinical management of different cancers. Ganetespib (GAN) is a well-established hsp90 inhibitor with enhanced pharmacological properties in comparison with its first-generation counterparts. Previous preclinical studies have shown that GAN exerts significant effects against cancer cells; however, its therapeutic effects against non-small cell lung cancer (NSCLC) A549 cells, achieved by modulating the expression of the NF-κB/p65 signaling pathway, remains unexplored. In this study, the combinatorial effect of GAN and methotrexate (MTX) against lung carcinomas was investigated through both in silico and in vitro studies. A combinatorial treatment regimen of GAN/MTX exerted more significant cytotoxic effects (p < 0.001) against A549 cells than individual treatments. The GAN/MTX combination also instigated nuclear fragmentation followed by augmentation in intracellular ROS levels (p < 0.001). The elevated ROS in A549 cells upon exposure to GAN/MTX combinatorial regimen was concomitantly accompanied with a remarkable reduction in mitochondrial viability. In addition, it was observed that the GAN/MTX combination succeeded in elevating caspase-3 activity and downregulating the expression levels of anti-apoptotic mediators Bcl2 and survivin in NSCLC A549 cells. Most importantly, the GAN/MTX combinatorial regimen impeded the activation of the NF-kB/p65 signaling pathway via repression of the expression of E-cadherin and N-cadherin, which was confirmed by molecular docking studies. Collectively, these findings demonstrated the synergistic effect of the GAN/MTX combinatorial regimen in suppressing the growth of A549 cells by modulating the NF-κB/p65 signaling pathway.